Learning Evaluation in Islam: Review of the Concept of the Qur'an and Hadith for Effective Education - Bahiyah, Khoridatul; Antika, Aisyah Nindi; Ishmah Sy, Ishmah Sy; Kurnia, Fitri Ayu (PT. Riset Press International, 2025)
Evaluation in education is an important component in assessing the extent to which learning objectives are achieved. This study examines the concept of evaluation in Islamic education based on the Qur'an and Hadith, and explores its relevance and application in the context of modern education. In Islamic education, evaluation is not only limited to academic assessment, but also to students' moral and spiritual development. The Qur'an and Hadith provide a framework for understanding evaluation as a holistic process that includes intellectual, moral, and spiritual dimensions. This study highlights the importance of integrating these values into the modern education system to produce individuals who are not only academically intelligent, but also have strong character and spiritual awareness. Although there are challenges in implementing Islamic-based evaluation in modern education that focuses more on quantitative assessment, this study suggests that Islamic evaluation principles can enrich modern education, creating a balance between academic achievement and personal growth.